2002
DOI: 10.1159/000064247
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde Levels and the Factors Affecting These Levels in Homes in Perth, Western Australia

Abstract: Formaldehyde is a highly irritant gas commonly encountered in indoor environments. Domestic levels of formaldehyde may vary with building practices and climate and the aim of the present study was to investigate formaldehyde levels in 185 homes in Perth, Australia. The formaldehyde was monitored using a validated passive sampling technique. Levels were measured in four rooms of each house (living room, kitchen and large and small bedrooms). In 160 homes the monitoring was repeated 4–7 months later in a differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 24 publications
(22 reference statements)
1
24
1
1
Order By: Relevance
“…If kL is higher, the indoor concentration may decay significantly over a ten-year period due to depleted storage. However, observed indoor formaldehyde concentrations are rarely less than than 3-5 μg/m 3 above the outdoor levels (Dingle & Franklin, 2002;Park & Ikeda, 2006;Hun et al, 2010;Willem et al, 2013). Factors that could contribute to this discrepancy include: multiple storage media with different depletion times, storage capacity not as low as the lower estimate, and the introduction of new sources.…”
Section: Highly Charged Storage: Example Formaldehydementioning
confidence: 98%
See 2 more Smart Citations
“…If kL is higher, the indoor concentration may decay significantly over a ten-year period due to depleted storage. However, observed indoor formaldehyde concentrations are rarely less than than 3-5 μg/m 3 above the outdoor levels (Dingle & Franklin, 2002;Park & Ikeda, 2006;Hun et al, 2010;Willem et al, 2013). Factors that could contribute to this discrepancy include: multiple storage media with different depletion times, storage capacity not as low as the lower estimate, and the introduction of new sources.…”
Section: Highly Charged Storage: Example Formaldehydementioning
confidence: 98%
“…Sampling in nearly 300 homes in three subsequent summers, Park and Ikeda (2006) observed a decrease in indoor formaldehyde concentration in homes initially less than 6 months old. Dingle and Franklin (2002) reported the concentration tends to decrease if the home is less than 10 years old. Gilbert et al (2008) reported higher indoor formaldehyde concentrations in homes where new furniture was introduced in the past 12 months, and Park and Ikeda (2006) noted the level of total VOCs increased by a factor of two in homes that had been renovated in the past year.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…HCHO is ubiquitously found throughout the troposphere with levels ranging from a few ppt in clean background air conditions to a few tens of ppb in polluted atmospheres such as metropolitan areas or contaminated indoor environments (e.g. Dingle and Franklin, 2002;Koppmann and Wildt, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…39 Os níveis de formaldeído medidos em divisões distintas de 185 residências de Perth, Austrália, não revelaram diferenças significativas. 169 ), a um presumível limite a partir do qual podem ocorrer danos citotóxicos da mucosa nasal. Numa pesquisa recente em que foi aplicado um modelo para estimar a exposição por inalação a vários poluentes, tendo por base as concentrações medidas no projeto AIRMEX e o tempo passado pela população em vários microambientes (interior no lar, interior no trabalho ou escola, exterior e nos transportes), concluiu-se que uma fração significativa dos habitantes das cidades europeias está exposta a níveis que ultrapassam o limite de 30 µg m -3 (média de 30 min).…”
Section: Concentrações Em Salas De Aula E Relação Com Níveis No Exteriorunclassified